Work-life Balance and the Working Women: Studit of Women's Experience in Gender Commodity Perspective - Bernarda Prihartanti (Journal of Feminism and Gender Studies, 2024)
This article aims to reflect the experiences of working women and mothers with dual roles regarding how the discourse on work-life balance affects their respective lives. The research using an autoethnographic method complemented by a literature review. Data was obtained through personal experience and interviews with several female friends who work in big cities like Jakarta and Surabaya. The data was processed as a self-reflection through Robin Truth Goodman's 'gender commodity' perspective. Through the results of reflections on experiences in this article, several working women feel the influence of the work-life balance discourse, both directly and indirectly. The results of this research also show that work-life balance as a discourse is reproduced by neoliberalism for capitalist.